Visual Composition Analysis in Avengers: Endgame to Enhance Visual Aesthetics - Nolly Medya Putra; Anri Fadini (KINEMA: Jurnal Komunikasi dan Penyiaran, 2026)
This study analyzes visual composition in enhancing visual aesthetics in the film Avengers: Endgame (2019), directed by Anthony and Joe Russo. Film, as a medium of mass communication, conveys meaning not only through narrative and dialogue but also through visual language. This study applies Bruce Block’s Visual Structure Model, which identifies seven core visual elements: space, line, shape, tone, color, movement, and rhythm. A qualitative descriptive method was employed, with documentation of selected scenes and in-depth interviews with film practitioners as primary data sources. Data validity was ensured through source triangulation. The findings reveal that each visual element functions systematically and progressively to support narrative development and emotional communication. Space is constructed through deep layered compositions creating depth and immersion; lines guide emotional tone from stability to tension; shapes distinguish organic versus technological worlds; tone controls dramatic intensity through planned contrast ratios; color builds psychological mood through progressive palette shifts across narrative phases; camera movement functions as emotional semiotics placing audiences within the action; and rhythm governs the dramatic temporal arc from grief to resolution. These elements do not operate in isolation but form a coherent visual system that produces aesthetic experience simultaneously with narrative meaning. Interviews with film practitioners confirm that the effectiveness of visual composition depends on the coherence of all elements, careful pre-production planning, and the integration of cinematography with editorial thinking. The study concludes that visual composition in Avengers: Endgame constitutes an active communicative structure that deepens audience emotional experience and strengthens narrative meaning.